A new application model for mobile technologies. (1st September 2004) - Rupnik, Rok; Krisper, Marjan; Bajec, Marko
The information society demands higher and higher productivity from people, which they indeed can achieve by using services and access information in the state of mobility. Mobile applications represent new application models that enable information support in the state of mobility. First, we discuss mobile applications in the context of information society, define their scope and limitations. Then we introduce a classical mobile application model, context, context-awareness, and context-aware mobile application model. In order to show the potential of information support in the state of mobility, we then discuss types of mobile applications and emphasise the significance of workflow concept for mobile applications.